2020
DOI: 10.1029/2020ef001587
|View full text |Cite
|
Sign up to set email alerts
|

Can Reservoir Regulation Along the Yellow River Be a Sustainable Way to Save a Sinking Delta?

Abstract:  The impact of reservoir regulation along the Yellow River on delta evolution was systematically evaluated  The man-made experiment through reservoir regulation along the Yellow River did mitigate delta erosion by scouring the lower river bed  With sediment coarsening of lower riverbed, bed scouring through reservoir regulation is not a sustainable way to nourish delta lobe Abstract Today's deltas are impacted negatively by 1) accelerated subsidence (e.g. from ground fluid extraction), 2) global eustatic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Sedimentation rate, another well‐established control of OC burial in coastal systems (e.g., Bao et al., 2018; Blair & Aller, 2012; Cui, Bianchi, Jaeger, et al., 2016), has been altered by many changes in the Anthropocene such as land‐use, precipitation gradients, eutrophication, and damming. In fact, the Eastern China Marginal Seas (ECMS), which has historically been fed by some of the most sediment‐rich rivers in the world, has been disproportionality altered by such human activities (e.g., Moon et al., 2020; Wu et al., 2020) ‐ due to profound economic growth in the region (He et al., 2014). The ECMS provides prolific gradients of change for exploration, and thus offers a unique set of natural laboratories to investigate these questions.…”
Section: Introductionmentioning
confidence: 99%
“…Sedimentation rate, another well‐established control of OC burial in coastal systems (e.g., Bao et al., 2018; Blair & Aller, 2012; Cui, Bianchi, Jaeger, et al., 2016), has been altered by many changes in the Anthropocene such as land‐use, precipitation gradients, eutrophication, and damming. In fact, the Eastern China Marginal Seas (ECMS), which has historically been fed by some of the most sediment‐rich rivers in the world, has been disproportionality altered by such human activities (e.g., Moon et al., 2020; Wu et al., 2020) ‐ due to profound economic growth in the region (He et al., 2014). The ECMS provides prolific gradients of change for exploration, and thus offers a unique set of natural laboratories to investigate these questions.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis in Figure 13 shows that the sediment discharge has a great contribution to the change of estuary area with a correlation of 0.615. Therefore, the impulsive delivery of muds and sands indeed transforms the present YRD from a destructive phase to an accretion phase [57]. However, this study shows that the contribution of sediment transport to the change of the estuary is not the only dominant factor.…”
Section: Critical Sediment Deriven By Human Activities and Climate Changementioning
confidence: 62%
“…Due to the coarsening of the surface bed material sediments, the erosion efficiency of the downstream riverbed has reduced. Since 2013-2017 in Figures 9 and 10, continuous scouring and reduced sediment transport have caused the current delta to re-enter a phase of erosion and destruction [57]. The previous study has shown that erosion of the abandoned delta lobes can sustain the supply of sediment to remote offshore depocenters, even after decades of declining river sediment discharge [58].…”
Section: Critical Sediment Deriven By Human Activities and Climate Changementioning
confidence: 99%
“…Furthermore, the shifting of the river course in the Yellow River Delta could enhance the progradation of the delta at the river mouth (Figure 6a-d) due to the relatively low sediment accommodation space at the nearshore area, i.e., the "Course Shift Bonus" proposed by [81]. Currently, although the Yellow River Delta is likely to keep prograding at the river mouth [43], the progradation could be unsustainable due to the functional degradation of the WSRS [51,82], suggesting a potential erosion of the delta under the projected continuous decrease of sediment load in the foreseeable future. Nevertheless, the potential shoreline retreat in the Yellow River Delta could possibly last for a while and transition to a new quasi-equilibrium as has already happened in the Volta River Delta [19,28].…”
Section: How Hydrological Alterations Affect Delta Morphologymentioning
confidence: 99%